The cardioprotective effect of inhibiting SGLT1 in hyperglycemia ischemia reperfusion injury. (3rd October 2022) - Almalki, A; Arjun, S; Bell, R; Yellon, D
Abstract: Background: Diabetes clinical trials have shown SGLT inhibition improves cardiovascular outcomes, yet the mechanism is not fully understood. Hyperglycemia is a common finding in diabetic and non-diabetic patients presenting with ACS and is a powerful predictor of prognosis and mortality. The role of hyperglycemia in ischemia-reperfusion injury (IRI) is not fully understood, and whether the Sodium Glucose Co-Transporter 1 (SGLT1) plays a role in infarct augmentation, before and/or after reperfusion, remains to be elucidated. Purpose: Investigate if SGLT1 is involved in a glucotoxicity injury during IRI and whether inhibiting SGLT1 with an SGLT1 inhibitor may reduce infarct size. Method: RT-PCR and in-situ hybridization (RNAScope) combined with Immunofluorescence integrated co detection with different cell marker techniques were used to detect SGLT1 mRNA expression in Sprague-Dawley whole myocardium and isolated primary cardiomyocytes. An Ex-vivo Langendorff ischemia-reperfusion perfusion model was used to study the effect of high glucose (22mmol) on myocardium at reperfusion. Canagliflozin (CANA) a non-selective SGLT inhibitor (1μmoL/L to block the SGLT1 receptor and SGLT2 and 5nmol/L to block only the SGLT2 receptor) and Mizagliflozin a selective SGLT1 inhibitor (100nmol/L) was introduced following ischemia at two different glucose concentration concentrations at reperfusion and its effect on infarct size measured using triphenyltetrazolium chloride (TTC) staining. Results: We showed that SGLT1 is homogenously expressed throughout the myocardium and is particularly evident within the vasculature. we demonstrate that hyperglycemia at reperfusion is injurious to myocardium with an increase of myocardial infarction. Our data reveal that glucose exacerbation of injury appears to be mediated via SGLT1. We have also demonstrated that high-glucose mediated injury in the isolated, perfused heart model is abrogated through the administration of a clinically available mixed SGLT2/SGLT1 inhibitor, canagliflozin, at a dose that inhibits both SGLT2 and SGLT1, but by the SGLT2-selective concentration. Conclusion: We have shown that SGLT1 is present in the myocardium. Hyperglycemia appears to augment myocardial infarction and inhibition of SGLT1 attenuates this incre Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The government of saudi Arabia